(Im)politeness Strategies Used in Vice -Presidential Candidates Debate Between Mike Pence and Sen. Kamala Harris - Nur Najibah Sukmawati; Tommy Hastomo; Purwanti Taman; Hana Lia; Lystiana Nurhayat Hakim (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Politeness is necessary for the way people socialize. However, some people choose to communicate impolitely despite knowing that it’s inappropriate. This study aims to find out how people use impoliteness strategies in communication, and identify the impoliteness strategies used in the Vice-Presidential United States of Amerika candidates debate between Mike Pence and Sen. Kamala Harris on October 8th, 2020, while also figuring out the purpose of using these strategies in the debate. For this reason, to identify the use of impoliteness strategies, the researcher used Jonathan Culpeper's (2005) theory of impoliteness strategies and a qualitative approach to analyze the data. The data was taken from a YouTube video entitled “Full Debate: Vice President Mike Pence and Sen. Kamala Harris | WSJ” posted by the Wall Street Journal on October 8, 2020. The results of this study revealed that four out of five impolite strategies were used, with negative impoliteness as the most commonly used strategy. The other four strategies are bald on record impoliteness, positive impoliteness, negative impoliteness, and sarcasm and mock politeness. Meanwhile, withholding politeness was never used in the debate.